Home Security System 4.0 Addition Uses Radio Frequency Waves - Parlindungan; Nugraha, Ucu (International Journal of Psychosocial Rehabilitation, 2020)
In this study, the authors will only limit the problems in assembly, communication devices using RF modules, MQTT connections, web sockets, and database analysis. The simulation is carried out with a model of a house with tools that will be controlled by a "full" system. "(Radio frequency (RF)-based home automation system IoT) has been successfully carried out, but for applications in the field certainly requires further research by adding parameters outside the scope of our research. Security systems are able to improve systems and can be controlled remotely, while the number of users and use of electrical devices can be monitored directly through the server in the form of cloud computing.